Air pollution control equipment selection guide - Schifftner, Kenneth C. (CRC Press, 2021)
"The third edition builds upon the sucesses of previous editions that developed a detailed discussion on various air pollution control equipment. It covers a wide range of equipment and provides a good overview of the related principles and applications. Very valuable are the practical examples that are not commonly available in typical books. Very easy to understand, especially for those who do not have formal training in air pollution control, this third edition considers the advanced technology developed in recent years. All chapters are updated and two new chapters on special applications of evaporators and optimization are added"--